Place Names and Enregistered Identity of Michigan's Upper Peninsula. (3rd July 2018) - Adams, Michael
Abstract : A clever reward system for frequent catalogue shoppers of Zingerman's – a renowned delicatessen in Ann Arbor, Michigan – uses Michigan place names to indicate spending and reward levels. In favoring those of Michigan's Upper Peninsula (UP), the item participates in the process of enregistering UP dialect.